Hubungan Pengetahuan, Dukungan Suami, Peran Bidan Dengan Kecemasan Menghadapi Persalinan Di TPMB Salmiah Kabupaten Belitung Timur : (Relationship Between Knowledge, Husband's Support, Role of Midwives and Anxiety Facing Childbirth at TPMB Salmiah, East Belitung Regency - Daturrohma, Mawa (Dohara POAJ, 2024)
Introduction: Anxiety is a psychological element that describes the feelings and emotional states one has when facing events in one's life. The psychological problem felt by pregnant women when facing childbirth is anxiety. Based on data from the Indonesian Ministry of Health in 2018 the incidence of anxiety among pregnant women in Indonesia reached 373,000,000.1 In the previous research 22,5% of mothers experienced mild anxiety; 30% moderate anxiety; 27% severe anxiety and 20% very severe anxiety. Factors include knowledge, husband's support and also the role of midwives. The aim of the research is to find out the relationship between knowledge of husband's support, and the role of midwives with anxiety facing childbirth at TPMB Salmiah. Methods: This type of quantitative research is descriptive analytical research and uses a cross-sectional design, research is carried out when data collection between the independent variable and the dependent variable is carried out together at the same time. Technique sampling uses total sampling, namely where the number of samples taken is equal to the population of 30 people. research instrument Questionnaire. The research time was in December 2023 at TPMB Salmiah. Data analysis used chi-square. Results: The Result Respondents were not anxious about childbirth namely 21 respondents (70%) had good knowledge about the birthing process namely 18 respondents (60%). Respondents received support from their husbands in facing the birthing process namely 25 respondents (83,3%). Respondents assess the role of midwives as good in providing information and support namely 25 respondents (83,3%) with a chi-square test result with a p-value of 0,05. So there is a relationship between knowledge, husband's support and the role of midwives with anxiety about facing childbirth at TPMB Salmiah in 2023. Discussion: Then there is a relationship between knowledge, husband support, implementation and the role of midwives with anxiety facing childbirth.